1991
DOI: 10.1063/1.348458
|View full text |Cite
|
Sign up to set email alerts
|

Graded band-gap ohmic contacts to n- and p-type InP

Abstract: W-Sb and W-In-Sb thin films were deposited by co-sputtering independent targets on n- and p-type InP wafers. The composition of the films was ascertained by monitoring the sputtering rate of each target. Au was sputtered on the back side and the sandwiched wafers were annealed in a quartz furnace to up to 400 °C. The conduction and diffusion characteristics of the films were studied as a function of the annealing temperatures. The Auger depth profile shows an outdiffusion of In to the surface of the WInSb film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…Similar contacts using either Mn or Mg in place of Zn were not ohmic [63], but a Pd/Zn/Pd contact without the use of Ge was fabricated with contact resistivity in the mid 10-5 Q-cm2 [60]. Finally, contacts based on reducing the surface semiconductor bandgap using W-In-Sb to p-type InP with contact resistivity in the low 10-5 range were also reported [59].…”
Section: Contacts To Inpmentioning
confidence: 99%
“…Similar contacts using either Mn or Mg in place of Zn were not ohmic [63], but a Pd/Zn/Pd contact without the use of Ge was fabricated with contact resistivity in the mid 10-5 Q-cm2 [60]. Finally, contacts based on reducing the surface semiconductor bandgap using W-In-Sb to p-type InP with contact resistivity in the low 10-5 range were also reported [59].…”
Section: Contacts To Inpmentioning
confidence: 99%
“…(Formation of a narrow bandgap intermediate semiconductor layer (ISL) such as InSb x P 1−x was previously proposed for the contacts with Sb. 5,20) However, InSb x P 1−x was not observed by XTEM with 1 nmφ probe. Therefore, it seemed that the added Sb would not benefit the narrow band gap ISL model.…”
Section: Role Of the Sb First Layermentioning
confidence: 94%
“…The ohmic contacts which have a narrow band gap intermediate semiconductor layer ͑ISL͒ such as InSb x P 1Ϫx were previously proposed. 7,20 However, the details of the interfacial microstructure, especially the ISL/InP interfacial structure, were not reported. From the quasibinary phase diagram study on the InP-InSb system, it was reported that solid solutions were formed only in limited regions: x is nearly zero or x is nearly one in the InSb x P 1Ϫx formula.…”
Section: A Ohmic Contact Formation Mechanismmentioning
confidence: 95%